2000
DOI: 10.1055/s-2000-11135
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective Effect of Apocynum venetum and its Active Constituents

Abstract: The leaves of Apocynum venetum L. are used as a tea material in north China and Japan. A water extract (500 mg/kg/day, one week administration) of the leaves of A. venetum showed protective effects against carbon tetrachloride (CCl4, 30 microliters/mouse) or D-galactosamine (D-GalN, 700 mg/kg)/lipopolysaccharide (LPS, 20 micrograms/kg)-induced liver injury in mice. Tumor necrosis factor-alpha (TNF-alpha) secreted from LPS-stimulated macrophages is the most crucial mediator in the D-GalN/LPS-induced liver injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 11 publications
4
62
0
2
Order By: Relevance
“…Similar results of the inhibitory effect of Oj extracts on HBsAg and HBeAg production in cultured 2.2.15 cells was also observed [19] . However, what the active part of Oj against HBV is is still unknown.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Similar results of the inhibitory effect of Oj extracts on HBsAg and HBeAg production in cultured 2.2.15 cells was also observed [19] . However, what the active part of Oj against HBV is is still unknown.…”
Section: Discussionsupporting
confidence: 83%
“…Histopathological examination also confirmed the function of OjF protecting the liver in DHBV-infected ducklings. Xiong Q et al [19] reported that Apocynum ventun extracts containing hyperoside and quercetin had hepatoprotective activity, and OjF contained these two compounds. These results demonstrated the antihepatitis B virus effect of OjF, which were consistent with antiviral activity of Oj [7,8] , making OjF a candidate for future evaluation in patients with HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, further investigation of the DNA polymerase level in HBV replication is required. Xiong et al [18] used the in vitro D-GalN/TNF-α model to confirm that many flavonoids, including hyperoside, protect liver cells from TNF-α-induced hepatocyte apoptosis. TNF-α has been found to be a very important pathogenic mediator in patients with alcoholic liver disease and viral hepatitis, as well as in many animal liver injury models [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Hyperoside (hyperin), quercetin-3-O-β-D-galactoside, is a flavonol glycoside which widely exists in many traditional medicines, such as Semen cuscutae [4] , St John's wort [5,6] , hawthorn [7] , Balbisia calycina [8] , and Alchornea cordifolia [9] . As an important bioactive compound, hyperoside has been documented to possess antiviral activity [10,11] , antinociceptive [12][13][14] , anti-inflammatory [15] , cardioprotective [7,16,17] , hepatoprotective [18][19][20] , and gastricmucosal-protective effects [21,22] . In previous studies, it has been shown that hyperoside demonstrates hepatoprotective properties in various chemically-induced hepatocyte injury models [18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation